2019
DOI: 10.1021/acsami.9b10474
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Conductivity of a Self-Healing Single-Ion Conducting Polymer Electrolyte, Poly(ethylene-co-acrylic lithium (fluoro sulfonyl)imide), for All-Solid-State Li-Ion Batteries

Abstract: Single-ion conducting polymer electrolyte (SICPE) is a safer alternative to the conventional high-performance liquid electrolyte for Li-ion batteries. The performance of SICPEs-based Li-ion batteries is limited due to the low Li+ conductivities of SICPEs at room temperature. Herein, we demonstrated the synthesis of a novel SICPE, poly­(ethylene-co-acrylic lithium (fluoro sulfonyl)­imide) (PEALiFSI), with acrylic (fluoro sulfonyl)­imide anion (AFSI). The solvent- and plasticizer-free PEALiFSI electrolyte, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 64 publications
2
60
1
Order By: Relevance
“…Polyanions in reports mainly include alkyl carboxylates, [ 108 ] sulfonates, [ 109 ] sulfonylimides, [ 110,111 ] and borates [ 112 ] in view of immobilized anions. Choosing an appropriate polyanion species is vital to the single‐ion conductor design.…”
Section: Macromolecular Design Of Polymer Matrixmentioning
confidence: 99%
“…Polyanions in reports mainly include alkyl carboxylates, [ 108 ] sulfonates, [ 109 ] sulfonylimides, [ 110,111 ] and borates [ 112 ] in view of immobilized anions. Choosing an appropriate polyanion species is vital to the single‐ion conductor design.…”
Section: Macromolecular Design Of Polymer Matrixmentioning
confidence: 99%
“…With the covalent attachment of anions to the polymer backbone, single lithium ion conducting polymer electrolytes show a lower ionic conductivity of 10 −7 to 10 −6 S/cm at room temperature (Cao et al, 2017(Cao et al, , 2020. Recent study demonstrated the remarkably high Li + conductivity of 5.84 × 10 −4 S/cm at 25 • C (Ahmed et al, 2019). Due to its flexible nature and good adhesive properties, polymer electrolytes components can form good contact with the electrodes.…”
Section: Hybrid Solid Electrolytes Polymer Matrixmentioning
confidence: 99%
“…As shown in Figure 4, healing of electrode cracks and interfacial damage is achieved by self‐healing solid polymer electrolyte with dynamic hydrogen bonding [ 75–78 ] or ionic bonding. [ 79 ] Zhou et al.…”
Section: Challenge and Opportunitiesmentioning
confidence: 99%
“…[ 78 ] D'Angelo and Panzer copolymerized two zwitterionic monomers to endow self‐healing properties to the solid polymer electrolyte, as an alternative approach besides hydrogen bonding. [ 79 ] The ionic conductivity of self‐healing polymer electrolyte is comparable with conventional solid polymer electrolyte, at around 10 −4 to 10 −5 S cm −1 at 298 K. [ 75–79 ] Whiteley et al. used self‐healing vitrimer as a binder for inorganic SE.…”
Section: Challenge and Opportunitiesmentioning
confidence: 99%